Corporate Governance Mechanisms and Managerial Optimism - Dariush Khorrami (Shahid Bahonar University of Kerman, 2017)
The purpose of this study is investigating the effects of corporate governance mechanisms on managerial optimism in the companies listed in the Tehran Stock Exchange, TSE. In previous studies on behavioral corporate finance, it was indicated that managerial optimism can affect the decisions about company’s activity that may lead to decreasing value of the activities. In this study, the statistical population consists of the companies listed in the TSE, and based on the sampling condition, 125 companies in the period 2010 to 2014 were selected. The collected information from the sample was used in estimation modelling of multiple regressions. In the sample, the optimist managers were recognized by their proxies of earnings forecast and the number of optimistic forecasts to the number of total forecasts. The findings from multiple regression model showed that among a number of chosen mechanisms of corporate governance, including managerial ownership, ownership concentration, and board characteristics, which include non-duality, board size and board independence, only managerial ownership and board independence may reduce the level of CEO’s optimism, and that the other variables have no significant effect on the dependent variable. In addition, it can be claimed that corporate governance should move towards new role entitled as behavioral corporate governance by recognition of behavioral bias.